Knowledge collaboration among tax professionals through the lens of a community of practice - Nurhidayah Bahar; Shamshul Bahri; Zarina Zakaria (Journal of Risk and Financial Management, 2022)
This paper presents knowledge collaboration among tax professionals in a tax-knowledge context within Malaysian accounting associations through the conceptual lens of a community of practice. Semi-structured in-depth interviews were conducted with a total of 29 tax professionals. Additionally, data were also gathered from field notes and archival data. The findings revealed that the Malaysian accounting-professional associations reflected a community of practice. Knowledge collaboration occurs among members in this community in order to attain the highest standard of technical and professional competency in tax knowledge and practice. The findings from this study complement and expand previous research on CoP, knowledge management, and collaboration. The findings suggest exploring a better strategy to implement a central repository of knowledge acquired or generated by the members within the community to support the learning lifecycle.
Keywords: 650; knowledge collaboration; community of practice; knowledge management; taxation; tax knowledge; tax system